PV generator and energy storage systems for laboratory building - Ismail El Kafazi; Maryam Lafkih; Rachid Bannari (Energy Reports, 2020)
A microgrid contains a PV generator and energy storage system connected in a laboratory building. Power generation is scheduled to meet the load of the building to adjust optimally the generation exchange within the microgrid. In this study, the problem of decreasing the cost of energy under varied system constraints and user decisions is addressed. In addition, minimizing electricity costs of the utility grid is proposed as an optimization model. To minimize the using of the grid, ESS is scheduled according to the peak demand. The proposed algorithm schedules the charging and discharging of the battery. A switching control technique is implemented for optimal scheduling of the hybrid system. Simulation is performed using GAMS, the obtained results validate that the intended model can minimize the operation cost.
Keywords: 330; Optimization; Day ahead; Energy management; Multi objective scheduling; PV generation